Noninvasive Systemic Modalities for Prevention of Head and Neck Radiation-Associated Soft Tissue Injury: A Narrative Review - Kim, Leslie N.; Rubenstein, Robyn N.; Chu, Jacqueline J.; Allen, Robert J., Jr.; Mehrara, Babak J.; Nelson, Jonas A. (Journal of Reconstructive Microsurgery, 2022)
Background Radiation-associated soft tissue injury is a potentially devastating complication for head and neck cancer patients. The damage can range from minor sequelae such as xerostomia, which requires frequent daily maintenance, to destructive degenerative processes such as osteoradionecrosis, which can contribute to flap failure and delay or reverse oral rehabilitation. Despite the need for effective radioprotectants, the literature remains sparse, primarily focused on interventions beyond the surgeon's control, such as maintenance of good oral hygiene or modulation of radiation dose.Methods This narrative review aggregates and explores noninvasive, systemic treatment modalities for prevention or amelioration of radiation-associated soft tissue injury.Results We highlighted nine modalities with the most clinical potential, which include amifostine, melatonin, palifermin, hyperbaric oxygen therapy, photobiomodulation, pentoxifylline–tocopherol–clodronate, pravastatin, transforming growth factor-β modulators, and deferoxamine, and reviewed the benefits and limitations of each modality. Unfortunately, none of these modalities are supported by strong evidence for prophylaxis against radiation-associated soft tissue injury.Conclusion While we cannot endorse any of these nine modalities for immediate clinical use, they may prove fruitful areas for further investigation.
Keywords: radiation injury; head and neck cancer; prophylactic